2018
DOI: 10.1177/0020764018792585
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver depression: The contributing role of depression in patients, stigma, social support and religiosity

Abstract: Our findings suggested that the severity of patient depression and personal stigma of the caregivers were significant factors correlated with caregiver depression. Therefore, beyond optimizing the treatment of depression in patients, the issue of stigma among caregivers also needs to be addressed as a potential target of intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 57 publications
1
24
0
1
Order By: Relevance
“…The stigma around mental health issues was depicted in a variety of studies. This review revealed negative stereotypes, prejudice, and discrimination from society, the stigma attached to seeking mental help and mental health issues, labeling individuals with mental health issues and avoiding interaction with them (Abdollahi et al, 2017; Abdul Kadir & Bifulco, 2010; Abdullah et al, 2016; Ahmad Ramli et al, 2017; Brown et al, 2017; Chang & Horrocks, 2006; K. S. Chen & Kok, 2017; Chin et al, 2018; Hanafiah & Tine Van, 2015; Hui Chien et al, 2016; Ibrahim et al, 2019; Jacob et al, 2015; Khan, Sulaiman, et al, 2009; Khan, Syed Sulaiman, et al, 2009; Khan et al, 2011; Loo & Furnham, 2012, 2013; W. Y. Low et al, 1995, 1996; J. X. T. Ng et al, 2010; Razali & Ismail, 2014; Russell et al, 2018; Shobana & Saravanan, 2014; Yeap & Low, 2009; Zaini et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stigma around mental health issues was depicted in a variety of studies. This review revealed negative stereotypes, prejudice, and discrimination from society, the stigma attached to seeking mental help and mental health issues, labeling individuals with mental health issues and avoiding interaction with them (Abdollahi et al, 2017; Abdul Kadir & Bifulco, 2010; Abdullah et al, 2016; Ahmad Ramli et al, 2017; Brown et al, 2017; Chang & Horrocks, 2006; K. S. Chen & Kok, 2017; Chin et al, 2018; Hanafiah & Tine Van, 2015; Hui Chien et al, 2016; Ibrahim et al, 2019; Jacob et al, 2015; Khan, Sulaiman, et al, 2009; Khan, Syed Sulaiman, et al, 2009; Khan et al, 2011; Loo & Furnham, 2012, 2013; W. Y. Low et al, 1995, 1996; J. X. T. Ng et al, 2010; Razali & Ismail, 2014; Russell et al, 2018; Shobana & Saravanan, 2014; Yeap & Low, 2009; Zaini et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the findings of this review show that a lot more work needs to be done on individuals with psychiatric illnesses as well as their caregivers owing to the presence of stigma in the community about mental health issues. Caregivers have been found to have different mental health problems due to the burden of care, discriminatory attitudes towards individuals with mental health problems and inadequate mental health knowledge (Ahmad Ramli et al, 2017; Chang & Horrocks, 2006; Chin et al, 2018; Chu et al, 2018). The MHL needs to be comprehensively investigated in student population as well owing to increasing rates of mental health issues in them.…”
Section: Discussionmentioning
confidence: 99%
“…It leads to an emotional and physical burden for the caregivers. Studies conducted (Chai, Mahadevan, Ng, Chan, & Md Dai, 2018) showed a significant relationship between stigma and depression in the caregivers. The study conducted by (Varghese et al, 2017)highlights the need for interventions that address the family needs such as providing knowledge about schizophrenia, which can affect the stigmatization process both positively and negatively.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, social support perceived as adequate or positive may be related to a less stressful situation and may favour the emotional well-being of older caregivers. Thus, emotional problems arising from the subjective burden on caregivers should be addressed as an objective of intervention by increasing social support [25]. However, to the best of our knowledge, no publication has studied the relationship between social support on mental well-being in older caregivers, previously.…”
Section: Introductionmentioning
confidence: 99%